Peran Orang Tua dalam Pembelajaran Daring terhadap Hasil Belajar Siswa Kelas 1 di SD IT Almubarok Palembang - Ida Larasati; Umi Nur Kholifah (Jurnal Spiritual Healing, 2022)
Parents as their children's companions in conducting online learning during a pandemic are very often disturbed, both from the aspect of poor internet connections, limited internet quotas, inadequate online learning media facilities, and problems with time so that the role of parents in accompanying their children in conducting online learning is not effective and affects learning outcomes as happened at SD IT Al Mubarok Palembang, this study aims to find out how the role of parents in online learning / e-learning on the learning outcomes of grade 1 students at SD IT Almubarok Palembang. The research method used is a case study with a descriptive qualitative approach, the research subjects are parents and teachers of SD IT Al Mubarok, data collection techniques are carried out through interviews, observation and documentation. Data analysis was carried out by reduction. The results showed that the role of parents as teachers was constrained by the minimal knowledge of parents. Then the role of the next parent as a facilitator has been carried out well even in the midst of economic limitations during the pandemic. Then the role as a motivator is carried out by parents by providing special time for children to keep the spirit of learning during the pandemic. Finally, the role of parents as directors is carried out by providing direction and advice by parents for children when carrying out online learning although in practice this is hampered by the busyness of parents. has not been carried out optimally.